The mucous covering of fecal sacs prevents birds from infection with enteric bacteria. (24th March 2014) - Ibáñez‐Álamo, Juan Diego; Ruiz‐Rodríguez, Magdalena; Soler, Juan José
<x xml:space="preserve">Abstract</x> Nestlings of many bird species produce fecal sacs, excrements encapsulated within a mucous covering. Although it facilitates parents' removal of feces from nests, which would improve hygienic conditions for developing nestlings, no functional (i.e. adaptive) explanation of fecal sac production has been previously investigated. We propose that the mucous covering would isolate enteric pathogenic bacteria, thereby preventing contamination of nestlings and parents. This antimicrobial hypothesis therefore predicts that density of bacteria would be drastically reduced from the inside to the outside of nestlings' droppings, and that the fecal sac covering would inhibit other bacterial grow. We tested these predictions by means of culturing bacteria obtained from different parts of the sac and inhibition tests. In accordance with the hypothesis, bacterial loads of the outside of fecal sacs were significantly lower than those estimated from the inside of the covering. In addition, we did not find evidence of antimicrobial activity of the covering, which suggests that the hypothesized bacterial isolation function is accomplished by a physical rather than a chemical protection. Bacterial density of the liquid that permeates out after 23 min does not differ with that estimated for the inside of the sac, suggesting short‐term effects of fecal sacs as bacterial barrier. These findings highlight the major role of bacterial infections as a selective pressure for explaining the evolution of traits that, as the covering of fecal sacs, facilitate nest sanitation in this group of animals.